A genome‐scale yeast library with inducible expression of individual genes. Issue 6 (7th June 2021) - Arita, Yuko; Kim, Griffin; Li, Zhijian; Friesen, Helena; Turco, Gina; Wang, Rebecca Y; Climie, Dale; Usaj, Matej; Hotz, Manuel; Stoops, Emily H; Baryshnikova, Anastasia; Boone, Charles; et al.
Abstract: The ability to switch a gene from off to on and monitor dynamic changes provides a powerful approach for probing gene function and elucidating causal regulatory relationships. Here, we developed and characterized YETI (Yeast Estradiol strains with Titratable Induction), a collection in which > 5, 600 yeast genes are engineered for transcriptional inducibility with single‐gene precision at their native loci and without plasmids. Each strain contains SGA screening markers and a unique barcode, enabling high‐throughput genetics. We characterized YETI using growth phenotyping and BAR‐seq screens, and we used a YETI allele to identify the regulon of Rof1, showing that it acts to repress transcription. We observed that strains with inducible essential genes that have low native expression can often grow without inducer. Analysis of data from eukaryotic and prokaryotic systems shows that native expression is a variable that can bias promoter‐perturbing screens, including CRISPRi. We engineered a second expression system, Z3 EB42, that gives lower expression than Z3 EV, a feature enabling conditional activation and repression of lowly expressed essential genes that grow without inducer in the YETI library. Synopsis: A conditional expression system is used to make >5, 600 genes inducible at their native loci with a small molecule that is otherwise inert in yeast. The resulting strain collection is systematically characterized using high‐throughput assays. All strains contain the SGA markers for high‐throughput genetics as well as unique molecular barcodes for functional genomics. A gene's native expression level is a critical parameter that can influence growth‐based assays in multiple species. Two systems Z3 EV and Z3 EB42, enable different types of growth‐based screens, and Z3 EV is ideal for studying transcriptional regulatory networks. The transcription factor Rof1 inhibits growth when overexpressed, and is a transcriptional repressor. Abstract : A conditional expression system is used to make > 5, 600 genes inducible at their native loci with a small molecule that is otherwise inert in yeast. The resulting strain collection is systematically characterized using high‐throughput assays.